Syarat Perlu atau Cukup F-bounded di dalam Ruang Metrik-a Fuzzy - Lukman Zicky; Mahmud Yunus (Limits: Journal of Mathematics and Its Applications, 2022)
Metrics have an important role in mathematics, both in analysis as well as applications. One of the new concepts of metric space is fuzzy -metric space. This metric space is an expansion of the fuzzy metric space by adding generator. In this paper, we discuss characterization of F-bounded in the fuzzy -metric space. The property of F-bounded is obtained from the compact subset of a given universe set. This characteristic has been discussed by Changqing and Kedian in Hausdorff fuzzy metric spaces. In this paper, the necessary and sufficient conditions are obtained so that the fuzzy -metric space satisfies the properties of F-bounded.